Mapping urban agriculture in Portugal: Lessons from practice and their relevance for European post-crisis contexts - Delgado Cecília (Moravian Geographical Reports, 2017)
A significant sample of twenty-nine Portuguese urban agriculture (UA) initiatives is analysed in this article. It argues that emerging initiatives are relevant for shifting from a post-crisis approach to one that is more developmental. This multi-level analysis finds that UA in Portugal: embraces allotment gardens, urban farms and short food chains; deals primarily with vegetables and fruit; takes place predominantly on public and institutional land; and is championed by municipalities and to a lesser extent by civil society initiatives. UA is predominantly a metropolitan phenomenon. Furthermore, activities are organised around three pillars: production of food; simple processing and distribution; and a significant set of capacity building and training activities. UA is recent phenomena in Portugal, and it has expanded quickly since the 2008 economic crisis. The paper explores in-depth four innovative short food chains from the sample of initiatives. They are led by young entrepreneurs, make positive use of social networks, are committed to social and economic values, and expanded successfully in generating jobs at the time of the crisis. These examples strongly suggest that UA social economy enterprises are a driving force behind integrated sustainable development approaches in European cities, if and when supported by public policies.